Descriptive ethnobotanical studies are needed for the rescue operation of documenting traditional knowledge - Łukasz Łuczaj (BMC, 2023)
Abstract In this essay, I claim that the primary aim of ethnobiological research is now to document disappearing traditional knowledge. This is an absolute priority due to the rate at which biocultural biodiversity in the world is disappearing. Rather than diverting our efforts into inflating the theoretical part of ethnobotany, we should concentrate on knowledge documentation to facilitate its circulation in the communties that hold it or at least to preserve it for future generations, even in the static form of databases or video recordings.